The Position of the Court of Cassation on the Proof of Desertion Claims: An Analytical Study - Taha, Aqeel (Journal of Legal Sciences, 2026)
This research discusses the position of the Federal Court of Cassation regarding the proof of a claim of abandonment as one of the delicate personal status claims that affect the stability of the family and require careful and balanced judicial treatment. It focuses on explaining the direction of the judiciary in interpreting the concept of abandonment, identifying its legal elements, and distinguishing it from other forms of separation, while linking this to the provisions of the Personal Status Law and the Iraqi Civil Procedure Law in force. The research also analyzes the court’s methodology in assessing evidence, particularly personal testimony and circumstantial evidence, and their sufficiency to convince the court of the fact of abandonment without legitimate excuse. We adopted a comparative analytical approach by reviewing Iraqi judicial applications and comparing them with Emirati and Jordanian legislation, while also drawing on aspects of comparative jurisprudence. The research showed that the Court of Cassation tends to be relatively strict in proving a claim of abandonment and imposes careful control over the conviction of the lower court in concluding the fact of abandonment. It also showed that the judiciary is not satisfied with the mere claim, but requires clear evidence proving the continuation of abandonment for a considerable period with the absence of a legitimate justification according to the circumstances of each case. This research concluded that the burden of proof falls on the plaintiff, while granting the court broad discretionary power in weighing and prioritizing evidence in accordance with the reality of the case and its circumstances. This revealed to us a general convergence between Iraqi and comparative jurisprudence in the stringency of evidentiary requirements, with only minor differences in the flexibility of acceptable means of proof.